Family Burden, Emotional Distress and Service Satisfaction in First Episode Psychosis. Data from the GET UP Trial - Ruggeri, Mirella; Lasalvia, Antonio; Santonastaso, Paolo; Pileggi, Francesca; Leuci, Emanuela; Miceli, Maurizio; Scarone, Silvio; Torresani, Stefano; Tosato, Sarah; De Santi, Katia; Cristofalo, Doriana; Comacchio, Carla; et al. (Frontiers in Psychology, 2017)
Background Literature has documented the role of family in the outcome of chronic schizophrenia. In the light of this, family interventions (FIs) are becoming an integral component of treatment for psychosis. The First Episode of Psychosis (FEP) is the period when most of the changes in family atmosphere are observed; unfortunately, few studies on the relatives are available. Objective To explore burden of care and emotional distress at baseline and at 9-month follow-up and the levels of service satisfaction at follow-up in the two groups of relatives (experimental treatment EXP vs treatment as usual TAU) recruited in the cluster-randomized controlled GET UP PIANO trial. Methods The experimental treatment was provided by routine public Community Mental Health Centers (Italian National Health Service) and consisted of Treatment as Usual plus evidence-based additional treatment (Cognitive Behavioral Therapy for psychosis for patients, Family Intervention for psychosis and Case Management). TAU consisted of personalized outpatient psychopharmacological treatment, combined with non-specific supportive clinical management and informal support/educational sessions for families. The outcomes on relatives were assessed by the Involvement Evaluation Questionnaire (IEQ-EU), the General Health Questionnaire (GHQ-12), and the Verona Service Satisfaction Scale (VSSS-EU). Differences within and between groups were evaluated . Results At baseline, 75 TAU and 185 EXP caregivers were assessed. In the experimental group 92% of relatives participated in at least 1 family session. At follow-up both groups experienced improvement in all IEQ and GHQ items, but caregivers belonging to the EXP arm experienced a significantly greater change in 10 IEQ items (mainly pertaining to the ‘Tension’ dimension) and in GHQ items. Due to the low sample size, a significant effectiveness was only observed for 2 IEQ items and 1 GHQ-12 item . With respect to VSSS data at follow-up, caregivers in the EXP arm experienced significantly greater satisfaction in 8 items, almost all pertaining to the dimensions ‘Relatives’ Involvement’ and ‘Professionals’ Skills and Behavior’. Conclusions The Family intervention for psychosis delivered in the GET UP PIANO trial reduced family burden of illness and improved emotional distress and satisfaction with services. These results should encourage to promote FIs on caregivers of first-episode psychosis